A Review of Chhanda (Meters) Found in Ashtanga Hridaya (AYUSHDHARA, 2023)
Sanskrit, the oldest language in the world also called the ‘language of Gods’ not without any reason. It is the language of the four Veda. Chhanda Shastra is one among the six Vedanga. It is an essential component of Sanskrit Literature.Ayurvedic literature composed thousands of years ago, were written in Sanskrit only. Most of the Ayurveda Acharya were expert in other Shastra like Chhanda, Vyakarana etc. Ashtanga Hridaya written by Acharya Vagbhata is one of the most revered compendia in India and abroad as well. It is also one of the treatises which is translated into many languages. It is in the form of Padya (poem) and hence makes it very popular for recitation and memorization.Meters or Chhanda are an important and essential part of Sanskrit poetry. It is this part that makes it different from the prose. Chhanda are of many types -important among them are Sama vritta, Ardha sama vritta and Vishama Vritta Chhanda.In this article, Sama Vritta Chhanda, a type of Akshara Chhanda found in Ashtanga Hridaya are explored and they are explained with examples. There are around 25 types of Sama Vritta Chhanda are found in Ashtanga Hridaya. The knowledge of these Chhanda may help in understanding the sutra better and recitation easier with proper rhythm.